Proceso de atención nutricional en paciente de 47 años sexo masculino con diagnóstico de hígado graso. - Moran Baidal, Anggy Lisseth (2024)
Fatty liver disease is defined by the presence of fatty infiltration in the liver that does not occur due to alcohol consumption, but rather due to other secondary causes of chronic liver disease. (Farias, 2017). This clinical condition comprises a broad spectrum of liver damage extending from steatosis to non-alcoholic steatohepatitis, fibrosis to cirrhosis. Most patients usually remain asymptomatic until the development of cirrhosis, considered the last stage of the disease. (Farias, 2017). This clinical case was carried out on a 47-year-old male patient who was admitted to the hospital with symptoms of fatigue, weakness, upper right abdominal pain and jaundice in the eyes. The objective of this case is to identify the nutritional status of the patient through anthropometric indicators (ABCD). The line of research with which the case was developed is health and well-being. The nutritional status of the patient was assessed, where it was observed that he has morbid obesity, for which a nutritional plan equivalent to 1689.2 kcal was created. The patient was followed up, showing that his way of eating has changed, and he also managed to lose weight.